Hubungan Anemia Pada Kehamilan Dengan Kejadian Ketuban Pecah Dini (KPD) Di RSUD dr. Adjidarmo Rangkasbitung - Yulica Aridawarni; Aulia Oktaviani (Akademi Kebidanan La Tansa Mashiro, 2021)
Premature rupture of membranes includes obstetric complications during pregnancy, obstetric complications can cause maternal and fetal death, Premature rupture of membranes at RSUD Dr. Adjidarmo Rangkasbitung has increased in 2017-2018 which is 9.2%. This has an impact on maternal mortality and infant mortality rates in Indonesia. This study aims to determine the relationship of anemia in pregnancy with the incidence of Premature rupture of membranes at RSUD dr. Adjidarmo Rangkasbitung in 2018. The research design used was a case control type research method using a Retrospective approach. The population in this study were all mothers giving birth at RSUD dr. Adjidarmo Rangkasbitung in 2018 which amounted to 3,139. The research sample was 18 respondents with a ratio of 1:1 (9:9). By using data collection from secondary data (register book).